2008
DOI: 10.1136/sti.2007.027508
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of human papillomavirus infection among fishermen along Lake Victoria Shore in the Kisumu District, Kenya

Abstract: The epidemiology of human papillomavirus (HPV) infection in men in Kenya is largely uncharacterized. We set out to determine the prevalence and determinants of HPV infection among sexually active fishermen along Lake Victoria in the Kisumu district of Kenya. METHODS:Genital swabs were obtained from 250 consenting fishermen from 18 beaches and a detailed sociodemographic questionnaire was administered. HPV positivity was determined by polymerase chain reaction amplification and detected by dot blot hybridisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 28 publications
5
35
0
Order By: Relevance
“…Similar observations about sexual risk behaviour and an association with HPV have been made in studies of men in SSA. [10,17,28] While the data on the protective effects of condoms are somewhat mixed, [35] evidence from African studies in men show a reduced risk of genital HPV infection associated with condom use. [10,28,36,37] Evidence from randomised controlled trials (RCTs) of MC has conclusively demonstrated the protective benefits of MC in reducing the risk of HPV prevalence and incidence.…”
Section: Factors Associated With Hpv Infectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar observations about sexual risk behaviour and an association with HPV have been made in studies of men in SSA. [10,17,28] While the data on the protective effects of condoms are somewhat mixed, [35] evidence from African studies in men show a reduced risk of genital HPV infection associated with condom use. [10,28,36,37] Evidence from randomised controlled trials (RCTs) of MC has conclusively demonstrated the protective benefits of MC in reducing the risk of HPV prevalence and incidence.…”
Section: Factors Associated With Hpv Infectionmentioning
confidence: 99%
“…[10,17,28] While the data on the protective effects of condoms are somewhat mixed, [35] evidence from African studies in men show a reduced risk of genital HPV infection associated with condom use. [10,28,36,37] Evidence from randomised controlled trials (RCTs) of MC has conclusively demonstrated the protective benefits of MC in reducing the risk of HPV prevalence and incidence. [17,36,38,39] Related findings from the trial in Kenya have highlighted less frequent bathing as a risk factor for HPV infection, which may be associated with poor genital hygiene in uncircumcised men.…”
Section: Factors Associated With Hpv Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Communities in border regions of Tanzania and elsewhere in East Africa comprise mobile groups such as fisher folk, seafarers, truck drivers, cross-border traders and a resident community. Even resident communities are relatively fluid; the border area attracts people, for longer or shorter periods of time, in search of business opportunities such as petty trade, sex-work or employment in small scale restaurants and bars around the border sites [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%